Cognition, culture, and the arts: interdisciplinary perspectives on narrating, understanding, and reading - Hanenberg, Peter; Hallet, Wolfgang (Passagem, 2021)
The volume shows in which sense the study of culture, literature and the arts contributes to the understanding of human cognition. It explores evolutionary substrates of narrative; the interfaces between culture, stories and cognition; the cognitive strengths and weaknesses of reading; and other techniques of sense-making in music and the arts